π-Spacer-Linked Bisthienopyrroles with Tunable Optical Properties - Bulumulla, Chandima; Gunawardhana, Ruwan; Gamage, Prabhath L.; Kularatne, Ruvanthi N.; Biewer, Michael C.; Stefan, Mihaela C. (Synlett, 2018)
Thieno[3,2-b]pyrrole is an effective nonconventional semiconducting building block that could be generated in gram quantities with relatively high overall yields. Three organic semiconductors containing thieno[3,2-b]pyrrole were synthesized in good yields without requiring time-consuming column purifications. The synthesis, optical and electrochemical properties were systematically investigated.1 Introduction2 Experimental3 Synthesis and Characterization4 Theoretical Calculations5 Optical and Electrochemical Properties6 Thermal Stability7 Fluorescence Experiments8 GIXRD Data9 Conclusions
Keywords: thieno[3,2-b]pyrrole; organic semiconductors; electrochemical properties